Outcomes after ABO incompatible pediatric liver transplantation are comparable to ABO identical/compatible transplant - Lemoine, Caroline P.; Brandt, Katherine A.; Keswani, Mahima; Superina, Riccardo (Frontiers in Pediatrics, 2023)
Background: ABO incompatible (ABOi) liver transplantation (LT) was initially associated with a higher incidence of vascular, biliary, and rejection complications and a lower survival than ABO compatible (ABOc) LT. Various protocols have been proposed to manage anti-isohemagglutinin antibodies and hyperacute rejection. We present our experience with a simplified protocol using only plasmapheresis. Methods: A retrospective review of all patients who received an ABOi LT at our institution was performed. Comparisons were made based on era (early: 1997-2008, modern: 2009-2020) and severity of disease (status 1 vs. exception PELD at transplant). A pair-matched comparison was done to patients who received an ABOc LT. p<0.05 was considered significant. Results: 17 patients received 18 ABOi LT (3 retransplants). Median age at transplant was 7.4 months (1.1-28.9). 66.7% patients were listed as status 1. Hepatic artery thrombosis (HAT) occurred in one patient (5.6%), there were 2 cases of portal vein thrombosis (PVT) (11.1%), and 2 biliary strictures (11.1%). Patient and graft survival improved in the ABOi modern era, although not significantly. In the pair-matched comparison, complications (HAT p=0.29; PVT p=0.37; biliary complications p=0.15) and survival rates were similar. Patient and graft survivals were 100% in the non-status 1 ABOi patients compared to 67% (p=0.11) and 58% (p=0.081) respectively for patients who were transplanted as status 1. Conclusion: ABO incompatible liver transplants in infants with a high PELD score have excellent outcomes. Indications for ABO incompatible transplants should be liberalized to prevent deaths on the waiting list or deterioration of children with high PELD scores.